Effect of service sire and AI operator on conception rates in AI bred buffalo population under field conditions - BHAVE, KAUSTUBH GAJANAN (Indian Journal of Dairy Science, 2017)
The present study was carried out to estimate the conception rate of artificially bred buffalo population based on effect of service sire and AI operator, under field condition. The study was conducted in five different agro climatic zones of India during the period from June, 2010 to December 2014. Multivariate logistic regression method was employed to estimate conception rate from 13,790 inseminations records. The overall mean conception rate of the buffaloes was 48.67 Â± 0.42 per cent. Service sire and AI operator showed significant variation in conception rate while no significant difference was found in conception rate due to year of insemination. Â Out of 73 AI operator, 69 operators is comparable, since the differences are statistically insignificant in spite of insemination records ranging from 35 to 645. Odds ratio of 2014 year was lower (OR: 0.93) than our reference value of year 2010. Highest odds ratio found in 2012 year with estimated conception rate 49.41 per cent. Odds ratio went on increasing from 2010 to 2012 and then declined till 2014. Among the 53 service sire included in the study, 3 service sire exhibited higher fertility which was statistically significant whereas only one service sire showed lower success rate than the rest of the service sire. The insemination records ranged in between 50 to 1107, the Odds ratio of 37 A.I. bulls were higher than reference value, mostly statistically non-significant. Therefore management can play important role in monitoring performance of AI operator and service sire in field condition.